Application of the STAD model in learning analysis of intrinsic elements of class X saga texts - Lestari, Eli Puji; Septiana, Ika; Sagino, Sagino (Institute of Computer Science (IOCS), 2024)
This research is motivated by the existence of constraint factors in Indonesian learning, one of which is that teachers in teaching in class are dominated by conventional methods and assignments, still using the lecture method without being balanced with the use of models that are in accordance with the material resulting in less interesting learning, this causes one of the factors of low student learning outcomes. This study aims to see the application of the STAD model in learning the intrinsic element analysis of saga texts in class X. This research is qualitative research, using descriptive analysis. The techniques used in data collection are interviews and observations. The subjects in this study were X-3 class teachers and X-3 grade students. Based on the results of research that has been carried out shows that the application of the Student Teams Achievement Division (STAD) model can be applied to learning intrinsic element analysis of class X saga texts, given evidence with student learning outcomes that have obtained above average, with this learning model can make students enthusiastic when learning Indonesian.